Pelayanan Penerbitan Paspor Dalam Keadaan Darurat (Pandemi Corona Virus Disease 2019 (Covid-19)) Di Kantor Imigrasi Kelas I Tpi Tanjung Priok - Ahsanta Maulana; Hedwig Adianto Mau; Mardi Candra (Ridwan Institute, 2022)
There are two main problems in this research, first regarding the impact of the emergency, in this case the Covid-19 pandemic, on the implementation of passport issuance services at the TPI Tanjung Priok Class I Immigration Office. Second, regarding the obstacles faced during the implementation of passport issuance services in an emergency (Covid-19 pandemic) at the TPI Tanjung Priok Class I Immigration Office. This research is a descriptive qualitative research, which means that the data collected is not in the form of numbers, but rather the data comes from interview texts, field notes, personal documents, and other official documents. The data collection method used in this research is triangulation, namely, literature study, interviews, and observation. The results of this study indicate that the Covid-19 Pandemic has an impact on public services, especially in the service of issuing passports at the TPI Tanjung Priok Class I Immigration Office. The government issued a Large-Scale Social Restriction policy to prevent the transmission of Covid-19. This policy is also supported by the Director General of Immigration regarding a Circular regarding Limitation of Immigration services, people must be able to adapt through changes in lifestyle in the Covid-19 situation which is called the New Normal Period. So in this case the issuance of a Circular on the Implementation of Immigration Duties and Functions in the New Normal Order Period. There were several obstacles in implementing passport issuance services during the Covid-19 pandemic at the TPI Tanjung Priok Class I Immigration Office.